Development of a toxin-selective immunotracer for in vivo detection of Clostridioides difficile infection by immunoPET - Mario González-Arjona; Lorena Cussó; Luis Alcalá; María Isabel González; Alexandra de Francisco; María Jesús Fernández-Aceñero; Dag Sehlin; Stina Syvänen; Emilio Bouza; Patricia Muñoz; Manuel Desco; Beatriz Salinas (EJNMMI Radiopharmacy and Chemistry)
Abstract Background Clostridioides difficile infection (CDI) is a major healthcare challenge that is associated with high morbidity and mortality. Current diagnostic methods are limited in terms of specificity and invasiveness, necessitating novel, non-invasive imaging techniques. In this study, we develop and evaluate an immunoPET radiotracer targeting C. difficile toxin B for in vivo detection of CDI in a murine model. Results The monoclonal antibody bezlotoxumab, was radiolabeled with [125I]I for in vitro characterization and with [89Zr]Zr for in vivo PET imaging, resulting in high radiochemical yields (75.36 ± 4.11% for [125I]I and 71.58 ± 8.19% for [89Zr]Zr) and purities (> 99.99% in both cases), with stable binding properties. PET/CT imaging 48 h post-infection in an animal model of CDI (C57BL/6 mice and ribotype 027 strain) demonstrated specific accumulation of [89Zr]Zr-DFO-Beztxab in the colon and cecum of infected mice, thus making it possible to distinguish CDI from dysbiosis without specific C. difficile infection and healthy controls. Findings were confirmed by PET-based quantification and ex vivo biodistribution. Conclusions We successfully developed an immunoPET radiotracer targeting toxin B for detection of CDI. Its application in an animal CDI model proved its capacity to detect the source of infection with high specificity, while avoiding confusion with non-specific inflammation.